Molecular cloning and analysis of the ruv gene of Escherichia coli K12 - Benson, Fiona Elizabeth (1988)
Mutations in the ruv gene of Escherichia coli K-12 result in an increased sensitivity to agents that damage DNA. Studies presented in this thesis demonstrate that the ruv gene product is required for conjugational recombination in certain genetic backgrounds. From this it was inferred that the role of the ruv gene product was in the recombination repair of daughter strand gaps and double strand breaks in damaged DNA. In addition, the ruv gene product is shown to be required for the efficient recovery of F' transconjugants in certain genetic backgrounds, suggesting that recombination between transferred F' and the recipient chromosome may be an obligatory event in these strains. Expression of ruv is regulated as part of the SOS response to DNA damage, by the lexA and recA gene products. The ruv gene product appears not to have any major role in its own regulation, however the basal level of expression of other SOS genes is increased in strains carrying ruv mutations. The ruv gene has been cloned on a 10.4kb HindIII fragment into the low copy number vector pHSG4l5, to give plasmid pPVA101, which has been demonstrated to complement the UV sensitivity of strains carrying any of the 10 different ruv mutations tested. Analysis of the proteins synthesised by pPVA101, its deletion derivatives, and derivatives with Tnl1000 insertions inactivating the ruv gene, allowed the identification of the ruv coding region, and suggested that the ruv gene encoded a 4lkd protein. In addition, regions of the cloned DNA coding for two further proteins of approximately 24kd and 33kd were identified. The sites of insertion of Mud(Ap)Rlac and Tn10 elements in the ruv gene were mapped, which allowed the direction of transcription to be determined, and suggested that the 4lkd protein may be cotranscribed with the 24kd protein from a promoter upstream of the smaller protein. This was substantiated by the demonstration that two of the ruv mutations studied were chromosomal inversions, one of which had its end point within the coding region for the 24kd protein, and by the isolation of an SOS inducible promoter derived from the region upstream of the 24kd protein. The nucleotide sequence of the ruv region revealed two open reading frames, designated ruvA and ruvB, with coding potential for proteins of 22087 daltons and 37177 daltons respectively, corresponding to the proteins with molecular weights estimated as 24kd and 41kd from SOS-polyacrylamide gels. A possible promoter, and two sequences with homology to the LexA binding site consensus sequence were identified upstream of the coding region of the 22kd protein. An amino acid sequence within the proposed RuvB protein was identified with homology to ATP binding sites of other proteins 950involved in DNA metabolism.